2022
DOI: 10.2471/blt.22.288569
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance to improve physical activity of children and adolescents

Abstract: The global transition to current low levels of habitual physical activity among children and adolescents began in the second half of the last century. Low physical activity harms health in both the short term (during childhood and adolescence) and long term (during adulthood). In turn, low physical activity could limit progress towards several sustainable development goals, undermine noncommunicable disease prevention, delay physical and mental health recovery from the coronavirus disease 2019 pandemic, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…With the release of such guidelines, there is an urgent need for validated “fit-for-purpose” assessment tools to measure 24-hour movement behaviours in children aged 0–5 years [ 8 , 9 , 13 ]. Valid and reliable measures of young children’s movement behaviours are necessary to monitor population-level trends in movement behaviours, evaluate scaled-up interventions to promote healthy movement behaviours, and make informed public health policy and practice decisions [ 14 ]. While device-based assessments of movement behaviours (i.e., accelerometers) are preferred and frequently employed in studies of young children, such methods are difficult to implement in policy and practice settings as well as large population-based studies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the release of such guidelines, there is an urgent need for validated “fit-for-purpose” assessment tools to measure 24-hour movement behaviours in children aged 0–5 years [ 8 , 9 , 13 ]. Valid and reliable measures of young children’s movement behaviours are necessary to monitor population-level trends in movement behaviours, evaluate scaled-up interventions to promote healthy movement behaviours, and make informed public health policy and practice decisions [ 14 ]. While device-based assessments of movement behaviours (i.e., accelerometers) are preferred and frequently employed in studies of young children, such methods are difficult to implement in policy and practice settings as well as large population-based studies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the important findings mentioned above, the effects of prior PA practice performed in childhood and adolescence on the health of the adult population have only recently been investigated. Childhood and adolescence are important phases of life [ 7 , 8 ], in which lifestyle habits such as the practice of PA were carried into adult life [ 9 , 10 ]. Silva et al [ 11 ] in a study analyzing the practice of PA performed through sports, observed that adults who practiced this type of PA in childhood and adolescence were less likely to have hypertension in adult life.…”
Section: Introductionmentioning
confidence: 99%
“…Current policies are clear about the importance of sport and PA: sport is healthy and there is still much to be achieve in the area of healthy lifestyles [ 42 ]; however, in low-, middle-, and high-income countries, PA levels are still insufficient [ 31 , 43 ]. Moreover, few low- and middle-income countries have PA policies, while policies have been well developed in many high-income countries, although often with very limited implementation [ 44 ]. In addition, for many families today, PA involves a financial cost and family time that not everyone has the resources to afford [ 45 ].…”
Section: Introductionmentioning
confidence: 99%